Kontribusi Kekuatan Otot Lengan Dan Tangan Terhadap Keterampilan Service Lob Dalam Permainan Bulutangkis Sisw Putri SMP Islam Al Hasanah Bengkulu - Arrendi Afrilliyan; Nurul Fajar Muslimah Ningrum (Journal on Education, 2024)
The aims of this research to scientifically analyze how the relationship between arm and hand muscle strength to service lob skills in badminton games. The formulation of the problem is how big the role of these two muscle strengths is in maximizing the skill of service lob shots in badminton. The research was conducted at the badminton court building of Al Hasanah Islamic Junior High School, Bengkulu city. The method used in this research is the correlation method using product moment statistics and double correlation objectively with a total sample of 30 female students from Al Hasanah Islamic Junior High School Bengkulu City selected using total random sampling technique. The resulting data states that Ho is rejected and Ha is accepted by showing that there is a significant contribution between X1 and X2 with Y. This shows that there is a positive relationship from arm muscle strength and hand muscles to the skill of hitting service lob of K = r2 x 100% = 92.16%. Thus, it can be concluded that there is a positive relationship between arm muscle strength and hand muscle strength on service lob hitting skills by 92.16%.